Prevalensi Alveolar Osteitis Pasca Operasi Impaksi Molar Ketiga Bawah pada Pria dan Wanita - Bambang Dwirardjo (Journal of Dentistry Indonesia, 2015)
Alveolar osteitis (AO) continues to be a significant postoperative problem associated with the surgical removal of impacted mandibular third molars. This study aims to investigate the prevalence differences of AO between female and male patients with postoperative surgical removal of these teeth. An ex post facto approach was used with a total of 60 cases of removed impacted third molars recorded from 24 female and 38 male patients. An incidence of AO was defined to imply a painful condition that occurs after the surgical removal of teeth, usually beginning 3 to 5 days after surgery. Also, on examination the tooth socket appears to be empty with a partially or completely lost blood clot, and the bone surfaces of the socket are exposed. The results were analyzed using Chi-square test and showed significant differences in the prevalence of AO between male and female patients (α≤ 0.05). The prevalence of AO was 41.7% in female and 16.7% in male patients. In conclusion, female patients show a significantly higher prevalence of AO than male patients.